The Impact Digitalization and Globalization on Income Distribution in Emerging Industrial Economies - Demir, Ömer; Cengiz, Orhan; Nas, Şahin (My University, 2023)
Digitalization is one of the most important indicators of technological development. More specifically, digitalization affects income distribution in different ways. Improvement in digital technologies promotes labor productivity and economic efficiency. Hence, how digitalization affects income inequality is required to obtain more evidence. This study investigates the distributional impact of digitalization in 29 Emerging Industrial Economies (EIEs) over the period 2000-2020. The cross-sectionally augmented autoregressive distributed lag (CS- ARDL) estimation results show that digitalization and globalization alleviate income inequality. Likewise, economic growth negatively affects income inequality. In contrast, political stability has a positive impact on income inequality. Moreover, the Dumitrescu-Hurlin (D-H) panel causality test result confirms the two-way causality between economic growth, globalization, political stability, and digitalization with income inequality.
Keywords: Globalization; Digitalization; Income Inequality; CS-ARDL; Emerging Industrial Economies